Upland rice from technological validation areas and community banks of seeds in Nicaragua - Peng, Yuan-Ching; Siles, Pablo; Zeledón, Yasser; Dorado, Hugo Andres; Rivera Palacio, Juan (International Cooperation and Development Fund - ICDF, Nicaragua, 2020)
This dataset contains 287 crop cycles for upland rice in 14 departments of Nicaragua that were collected in the period 2016 – 2018. In the dataset, 100 and 187 records came from technological validation areas and community banks of seeds, respectively. Each location was georeferenced. Variables such as cultivar, planting practices, harvest date, and region were also recorded. Finally, Worclim and soil data layers from INETER (Instituto Nicaragüense de Estudios Territoriales) were used to integrated weather and soil information for each crop cycle. (2018-06). (2018-06)